Zapisz wyrażenia, nie używając nawiasów, a następnie zredukuj wyrazy podobne.

a) 9a + (5a - 7) =

b) 7a - (3a + 6) =

c) (3u - 7v) + (6v - 5) =

d) (8u + 4v) - (2u + 5v) =
PLS FAST



Odpowiedź :

Odpowiedź:

a) 9a + 5a- 7= 14a - 7

b) 7a - 3a - 6= 4a - 6

c) 3u - 7v + 6v -5= 3u - 13v - 5

d) 8u + 4v - 2u - 5v = 6u + (-1v)

Szczegółowe wyjaśnienie:

Odpowiedź:

a)  9a + ( 5a-7)= 9a + 5a -7= 14a -7

b)   7a - ( 3a +6)= 7a -3a  -6= 4a-6

c)   ( 3u -7v) + ( 6v -5)= 3u -7v +6v  -5= 3u  -v -5

d)   ( 8u +4v ) - ( 2u +5v)= 8u +4v -2u -5v= 6u -v

Szczegółowe wyjaśnienie: